Tinjauan Yuridis Terhadap Peninjauan Kembali Dalam Peradilan Tata Usaha Negara Dalam Putusan Nomor 154 PK/TUN/2016 - Karnelia, Nazwa (JPNM Jurnal Pustaka Nusantara Multidisiplin, 2024)
ABSTRACT In the struggle for justice, the whole community wants to get its rights fairly. Not only the people, but the state institutions also have the right to justice in the eyes of the law. According to Article 263, paragraphs (1) and (2) of the Constitution, it is explicitly stated that only the Supreme Court or its heirs may apply for a decision. The other party was not explicitly mentioned, but it was the Attorney General. The debate over the Supreme Court's approval of the General Prosecutor's review has not yet been opened. The jurists, the legalists, and the scholars have spoken a great many words. Not a few of them disagree with the judgement of the Supreme Court, but some of them understand it. As a result of various academic discussions and research, it appears that the emerging perspective is coloured by a different background of understanding. Some people seem to be based on a strong understanding of the teachings of positivism, while others appear to be founded on a closer understanding of legal realism.In the conflict present in Decision No. 154 PK/TUN/2016, land disputes disputed rights between state institutions and family heirs. The re-examination carried out with new evidence by the petitioner determines whether it serves justice to the parties." Keywords : Judicial Review; Juridical Review ; State Administration